T. Mateo Sanguino, J. M. Lozano Domínguez, I. J. Fernández de Viana González et. al. (2020): "ScienCity 2019. Fomento de la Cultura Científica, Tecnológica y de Innovación en Ciudades Inteligentes". Universidad de Huelva, 70 pp. ISBN 9781658694988. - José María Morillas Alcázar (Erebea. Revista de Humanidades y Ciencias Sociales, 2020)
-